Surgical reconstruction using biomaterials: an integrative literature review (Research, Society and Development, 2021)
Introduction: Biomaterials have by definition any biocompatible substance, which is not a drug, synthetic or natural, that for a complete period, increases or replaces the function of a tissue or organ, being used in post trauma. Objective: to verify, within the existing literature, which are the biomaterials available and their best ways to be used in surgical reconstruction. Methodology: it consists of an integrative literature review on surgical reconstruction using biomaterials, based on the establishment of the research keywords, the crossing of the descriptors “biomaterials” was performed; “biocompatible materials/therapeutic use”; "graft"; “plastic surgery/rehabilitation”; “bioengineering”, in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO Information Services, in August 2021, considering studies published in the period between 2008 and 2021. Results and discussion: according to the results collected from scientific articles, there is a wide availability of biomaterials for reconstruction, where each type can benefit different individuals. Considering the range of biomaterials available, there is a different availability for each one, but the purpose is to bring benefits to the regenerative process to individuals. Conclusion: it is up to the professional to choose the best biomaterial available individually for each patient and clinical condition.